Development of a Hybrid Training Package of Narrative Counseling Based on Parebhasan Culture to Improve Counselor Skills in Madura - Nur Hidayah; M. Ramli; Lutfi Fauzan; Mariani Binti Md Nor; Rofiqoh Rofiqoh; Husni Hanafi; Nur Mega Aris Saputra (Yayasan Keluarga Guru Mandiri, 2024)
Multicultural counseling is an essential approach for counseling services in Indonesia, with thousands of cultures and local wisdom. Multicultural Counselling is one of the keys to understanding the student's views, characteristics, and values based on their cultural background. One of the multicultural counseling developments is integrating Madhura's Parebhasan into the narrative counseling model. This research aims to develop a hybrid training design to improve counselor skills using narrative counseling based on Madhura's Parebhasan. This research used ADDIE's model to develop the training program. Data collection from 20 counselors in Madura used the reflection and training test and performance observation form. Data analysis uses descriptive, graphical, correlation, and regression analysis. The research results show that mastery of the material and practices in training affect the counselor's performance. Five Madhura's Parebhasans are integrated and suitable for escalating the effect of the narrative counseling procedure. The hybrid training package of Narrative Counseling based on Parebhasan has been developed and validated in practice. This research suggests testing the effectiveness and evaluating the implementation for the specific needs and problems of the students.